Pengaruh Stres Kerja Dan Komitmen Organisasional Terhadap Kinerja Petugas RSUD Dr. Soedarso Pontianak - Udin Rinaldi (STIE 'INDONESIA' Pontianak, 2015)
The purpose of this study was to analyze the effect of job stress and organizational commitment to performance in the personnel RSUD Soedarso Pontianak. Independent variables of the study consisted of organizational commitment and job stress, while the dependent variable consisted of the performance of officers. Results of the study, a direct effect of job stress is negative and no significantly related to organizational commitment (p = 0.092 >α = 0.05, β = -0,277). Organizational commitment directly influence a positive and significant effect on the performance of officers as well as dominant (p = 0.035 <α = 0.05, β = 0.362), a direct effect Job Stress is positive but no significant effect on the performance of officers (p = 0.484 >α = 0.050; β = 0.117).